2020
DOI: 10.3727/108354220x15957949047195
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Features and Risk Perception as Determinants of Taking out Travel Insurance

Abstract: Despite numerous studies on ways to reduce travel risks, not much attention has been paid to factors that encourage tourists to take out travel insurance. The aim of this study is (1) to investigate whether the tendency of tourists travelling abroad to take out travel insurance differs depending on their socio-demographic features and their risk perception, and (2) to determine which of the examined variables are most useful in predicting the tendency to take out insurance. Based on questionnaire data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…First, this study considered travel insurance as an effective risk reduction behavior following the outbreak of COVID-19 and our findings are consistent with those of earlier studies (e.g., Sarman et al 2019;Zalech 2020;Lo et al 2011;Sonmez and Graefe 1998b). In our study, the perception of COVID-19 and the subsequent risk perception toward traveling emerged as important determinants of purchasing travel insurance, thereby confirming the role of travel insurance as a risk reduction behavior in tourists' decision-making process.…”
Section: Theoretical Implicationssupporting
confidence: 91%
See 3 more Smart Citations
“…First, this study considered travel insurance as an effective risk reduction behavior following the outbreak of COVID-19 and our findings are consistent with those of earlier studies (e.g., Sarman et al 2019;Zalech 2020;Lo et al 2011;Sonmez and Graefe 1998b). In our study, the perception of COVID-19 and the subsequent risk perception toward traveling emerged as important determinants of purchasing travel insurance, thereby confirming the role of travel insurance as a risk reduction behavior in tourists' decision-making process.…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…Earlier studies have shown mixed effects of demographics on risk perception and insurance purchase. In this study, the respondents' age presented an inverted "U"shaped effect on travel insurance purchase, and this result is consistent with those of Chou and Yao (2011), (Lo et al 2011), andZalech (2020). Moreover, the result showed that middle-aged respondents were more intent on purchasing travel insurance than their younger and older counterparts.…”
Section: Theoretical Implicationssupporting
confidence: 84%
See 2 more Smart Citations
“…Indeed, earlier studies (e.g. Karl et al, 2020; Sönmez and Graefe, 1998b; Zalech, 2020) have shown mixed effects on destination choice, risk perceptions, and risk reduction behaviours. In our study, the symmetric approach showed only age and past visit experience having significant effects on visit intention, whereas in the asymmetric approach, gender, age, and income had a certain degree of influence on visit intention.…”
Section: Discussionmentioning
confidence: 98%